A Heterogeneous Nanoscale Covalent Organic Framework Fluorescence Probe for Sensitive Detection of Hydrogen Sulfide. Issue 5 (22nd March 2021) - Ge, Xuan; Zhang, Houyong; Zhang, Chengxiao; Du, Mingyue
Abstract: New strategies for highly selective and sensitive detection of highly toxic environmental pollutants are still a pressing need. Here, through Cu 2+ metalated porous nanoscale covalent organic framework (NCOF), a novel heterogeneous NCOF fluorescence probe has been synthesized for sensitive and selectivity detection of hydrogen sulfide (H2 S). Upon H2 S addition, the Cu 2+ released from the CuCOF, accompanied by the fluorescence recovered of COF. As far as we know, NCOF has not been reported as fluorescence probe for H2 S detection. The as‐prepared nano CuCOF displays an excellent sensitive response to H2 S with a detection limit of 10 nM. In addition, such heterogeneous fluorescence probe exhibited high selectivity towards to H2 S relative to other thiols and anionic species. Moreover, the detection of H2 S was achieved successfully in different actual water samples. Abstract : A heterogeneous NCOF fluorescence probe has been synthesized for sensitive and selectivity detection of hydrogen sulfide (H2 S). After addition of H2 S, Cu 2+ ions are released from the porphyin ring, accompanied by fluorescence recovery.